ANALYSIS OF FACTORS RELATED TO USE OF ANTENATAL CARE SERVICES AT KARAWANG HOSPITAL YEAR 2023 - Anita, Nur; Andriani, Pratiwi (HEARTY, 2025)
Background: The impact if pregnant women do not take advantage of ANC visits at least 4 times is that high risks during labor are not detected early and abnormalities that occur during pregnancy are not detected and can increase mortality and morbidity rates. Objective: This study aims to determine the factors related to the utilization of ANC services at Karawang District Hospital in 2023. Method: This research is a cross-sectional study. The population of this study were all pregnant women who visited ANC at Karawang District Hospital, with a total sample of 103 pregnant women. Data collection was carried out using questionnaires. Hypothesis testing was carried out using the Chi-Square test at a significance level of 0.05. Results: The research results show that: (1) there is a relationship between age and the use of ANC services, with p-value (0.033) < 0.05; (2) there is a relationship between education level and utilization of ANC services, with p-value (0.011) < 0.05; (3) there is a relationship between employment status and utilization of ANC services, with p-value (0.007) < 0.05; (4) there is a relationship between family income level and utilization of ANC services, with p-value (0.003) < 0.05; and (5) there is a relationship between the number of family members and the use of ANC services, with p-value (0.028) < 0.05.